The effects of guided imagery and relaxation technique on psychological functioning of children with cancer : a randomized controlled trial - Adi, Nurul Shafira (2018)
Relaxation technique is one of helpful tools for children coping with stress. It promotes long-term health by slowing down the body and quieting the mind. Guided Imagery Relaxation (GIR) technique has been developed and piloted to help children with cancer in Malaysia. This study measures the effectiveness of GIR technique in reducing children’s negative emotions and in improving their psychological functioning when they are receiving treatment for cancer. In particular, the study measures differences in scores of The Paediatric Quality of Life Inventory 4.0 (PedsQL) and PedsQL(VAS) scale as reported by parent and children before and after their children receiving GIR. Sixty (N=60) children with cancer participated in this study. Children who are diagnosed with cancer and fulfilled the inclusion criteria were recruited from paediatric oncology ward 6 Utara, (HUSM). Using parent-proxy and children report, the VAS and PedsQL were administered before the intervention of GIR. The children were given an individual MP3 player and they were guided on how to use the player and listen to the scripts, so that they will experience relaxation. The intervention involved of hearing the audio for three times a week, in three subsequent weeks (i.e. 3 times a week for 3 weeks). At the end of third week, post-intervention assessments were administered. Mixed ANOVA design were conducted to examine the differences in scores of VAS and PedsQL between intervention and control group before and after the intervention as reported by parents and children. There are significant decrease in domains of children’s Total symptom score, Anxiety,and Sadness, in VAS parent-reported from pre-intervention (M=31.3, (SD=21.9); M=26.3, (SD=25.9); and M=27.3, (SD=22.2) to post-intervention (M=10.5, (SD=7.9); M=8.57, (SD= 7.55); and M= 10.0, (SD=8.60) ( p < 0.001). There is no statistical significant difference in scores of PedsQ as well as child-reported VAS scale (p > 0.05) However, in all domains of PedsQL in intervention group, the scores increased which means parents reported better quality of life and psychological functioning in their children after receiving GIR intervention. In conclusion, GIR technique is an effective tool that helps to reduce negative emotions especially anxiety and sadness in children with cancer. This GIR tool has potential in helping children to manage their stress.